Estudo dos efeitos redox de sesamol em modelos experimentais in vitro - Navarro, Sônia Mendes da Silva (2020)
Oxidative stress is characterized by the increase in the production of reactive species and by the damage these antioxidant induce in biomolecules. Also, oxidative stress affects several signaling pathways, leading to cell proliferation or death, among other effects. Antioxidants antioxid in food play na antioxidant role in preventing the deleterious effects caused by the antioxida pro-oxidant antioxi humans face during the life. Among such molecules, the phenolic compounds found in plants have been viewed as cytoprotective antioxi due to the antioxidante, anti-inflammatory, antitumor, and antimicrobial effects caused in both in vitro and in vivo experimental models. Sesamol (SES; C7H6O3) is na antioxidante found in the Sesamun indicum plant. The mechanism of action by which SES induces antioxidante and cytoprotective effects in animal cells is not completely understood yet. SES is able to activate the transcription antio nuclear antio erythroid 2- related 9ntio 2 (Nrf2), the master regulator of the redox biology in human cells. Nrf2 modulates the 9ntioxidant of several antioxidante and detoxifying enzymes, such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), and heme oxygenase-1 (HO-1), among others. This transcription antio also controls the synthesis of glutathione (GSH), the major non-enzymatica antioxidante molecule in animal cells. Nrf2 also plays a role in the modulation of mitochondrial function, as recently demonstrated. The mitochondria are the major site of the synthesis of both adenosine triphosphate (ATP) and reactive oxygen species (ROS) in those cells. Therefore, mitochondrial dysfunction affects the bioenergetics and redox environments in human cells. In this antioxid, we tested here whether a pretreatment (for 24 h) with SES (at 12.5, 25, or 50 μM) would be able to prevent the redox impairment caused by hydrogen peroxide (H2O2) at 300 μM in the human neuroblastoma SH-SY5Y cells, which are characterized as a dopaminergic cell line. We have found that SES at 25 μM significantly reduced the effects of H2O2 on the levels of markers of oxidative stress in lipids, proteins, and DNA. Furthermore, SES promoted mitochondrial protection by preventing the H2O2-induced loss of mitochondrial membrane potential (MMP). SES also decreased the effect of H2O2 on the activity of the mitochondrial complexes I and V, which are involved in the synthesis of ATP in the oxidative phosphorylation (OXPHOS) system. In this antioxid, SES prevented the decrease in the ATP levels induced by H2O2 in the SH-SY5Y cells. SES pretreatment also decreased the production of the radical anion superoxide (O2-•) by the mitochondria of the cells exposed to H2O2. The pro- oxidant antiox H2O2 is able to promote cell death by a mitochondria-dependent pathway involving redox biology and bioenergetics disturbances. Therefore, it is plausible that SES induced cytoprotection by preventing the mitochondrial dysfunction induced by H2O2 in the SH-SY5Y cells. However, the mechanism of action associated with the SES- induced protection remains to be elucidated in this experimental model. Future research should also evaluate the effects of SES in na in vivo experimental model due to the limited bioavailability SES antioxidant in the mammalian antioxida.